Area of combined surgical interventions, including those with an angiosurgical component, in terms of malignant non-organ retroperitoneal tumors’ treatment - O. I. Kit; A. A. Maslov; E. N. Kolesnikov; O. V. Katelnitskaya; M. A. Kozhushko; A. V. Snezhko; T. B. Katsieva; R. E. Myagkov; S. V. Sanamyants; A. E. Anisimov; K. V. Kolomiets (Южно-Российский онкологический журнал)
Purpose of the study. To analyze the immediate outcomes following surgical treatment of locally advanced malignant non-organ retroperitoneal tumors (NRT).Materials and methods. Surgical interventions for malignant NRTs were performed in 114 patients at Abdominal Oncology Department № 1, National Medical Research Centre for Oncology.There were 48 males and 66 females among them. According to the histological structure, liposarcoma was commonly detected in 64 (56.1 %) cases.Results. Intraoperative revision revealed the spread of the tumor to adjacent anatomical structures in 67 (58.8 %) cases. Resection surgical interventions were performed in 109 patients, of which 106 (97.2 %) patients had operations performed in an amount of R0. Combined surgical interventions for NRTs were performed in 62 (54.4 %) patients, and multiorgan happened to be in 45 (72.6 %) patients out of those. Resection of the inferior vena cava was performed in 12 patients. Resection of the superior mesenteric vein was performed in 2 patients and the iliac-colonic vein in 2 patients. In 1 observation the left renal vein was resected with suturing of the lateral defect of the vessel wall. Complications during surgery and in the early postoperative period were noted in 14 (12.3 %) patients. In total, 2 patients died after operations, the mortality rate was 1.8 %.Conclusions. Tumor invasion of big main blood vessels is not a contraindication for surgical treatment of locally spread malignant non-organ retroperitoneal tumors.